Stakeholders Synergy in Accelering MSME (UMKM) Halal Certification Through Halal Self-Declare - Herdifa Pratama (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
A series of halal product guarantee regulations in Indonesia starting from Law Number 33 of 2014 until Government Regulation Number 39 of 2021 mandates that every MSME’s actor has a halal certificate on their products. In order to answer this mandate, a halal self-declare process was initiated to make it easier for MSME’s actors. This paper is a critical study of the halal self-declare which contains the pros and cons of acceleration and the consequences in it. This critical study aims to explore the synergy of stakeholders in halal certification effort for MSME through self-declare. The qualitative analysis of this study shows that the implementation of the self-declare flow requires solid synergy. Starting from the MSME’s actors, Ministry of Finance, Ministry of Investment, Halal Product Process Assistance, MUI, to the Organizing Agency of Halal Product Guarantee Organizing Agency, they have an active contribution in the self-declare flow. This synergy from the contribution of stakeholders will then optimize the halal self-declare as an acceleration of MSME’s halal certification and minimize the consequences that could potentially occur in the MSME’s self-declare